Filter Membrane Effects on Water‐Extractable Phosphorus Concentrations from Soil. Issue 2 (1st March 2018) - Norby, Jessica; Strawn, Daniel; Brooks, Erin
Abstract : To accurately assess P concentrations in soil extracts, standard laboratory practices for monitoring P concentrations are needed. Water‐extractable P is a common analytical test to determine P availability for leaching from soils, and it is used to determine best management practices. Most P analytical tests require filtration through a filter membrane with 0.45‐μm pore size to distinguish between particulate and dissolved P species. However, filter membrane type is rarely specified in method protocols, and many different types of membranes are available. In this study, three common filter membrane materials (polyether sulfone, nylon, and nitrocellulose), all with 0.45‐μm pore sizes, were tested for analytical differences in total P concentrations and dissolved reactive P (DRP) concentrations in water extracts from six soils sampled from two regions. Three of the extracts from the six soil samples had different total P concentrations for all three membrane types. The other three soil extracts had significantly different total P results from at least one filter membrane type. Total P concentration differences were as great as 35%. The DRP concentrations in the extracts were dependent on filter type in five of the six soil types. Results from this research show that filter membrane type is an important parameter that affects concentrations of total P and DRP from soil extracts. Thus, membrane type should be specified in soil extraction protocols. Core Ideas: Filter membrane type is rarely specified in method protocols for P analysis. Many different types of filter membranes are available. Results show that filter membrane type affects concentrations of P from soil extracts. Membrane type should be specified in soil extraction protocols for P analysis.